2020
DOI: 10.3390/ijerph17155609
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Impact of Lean Healthcare on Inpatient Care: A Systematic Review

Abstract: Healthcare services are facing challenges in increasing their efficiency, quality of care, and coping with surges in demand. To this end, some hospitals have implemented lean healthcare. The aim of this systematic review is to evaluate the effects of lean healthcare (LH) interventions on inpatient care and determine whether patient flow and efficiency outcomes improve. The review was performed according to PRISMA. We used six databases to search for studies published from 2002 to 2019. Out of 5732 studies, 39 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
54
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 157 publications
(315 reference statements)
4
54
1
3
Order By: Relevance
“…Accordingly, the literature published about the VSM methodology in healthcare organizations has been growing, with certain ups and downs, over the years. The trend is similar to the publications on the lean approach in the healthcare sector [156,157]. It is a trend which is not exponential, as has happened with the publications of other operations management tools, such as the healthcare supply chain [156].…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Accordingly, the literature published about the VSM methodology in healthcare organizations has been growing, with certain ups and downs, over the years. The trend is similar to the publications on the lean approach in the healthcare sector [156,157]. It is a trend which is not exponential, as has happened with the publications of other operations management tools, such as the healthcare supply chain [156].…”
Section: Discussionsupporting
confidence: 74%
“…Taking into account the results shown in the articles reviewed in this study, the implementation of VSM is a potent tool to reduce waiting times for the patients. Also, the development of VSM improves patient flow and efficiency, similar to other tools related to lean healthcare [153,[157][158][159]. The improvements have mainly come by way of reducing wasted time [160][161][162][163], and improving service quality, patient satisfaction [162,164,165] and safety [162,166,167].…”
Section: Discussionmentioning
confidence: 99%
“…Recent research [ 9 , 10 , 11 , 12 , 13 ] highlighted the Lean philosophy as a strategy allowing companies in any sector to adapt to rapid changes in the market, in the economy, in technical and social complexity issues, and in the needs of customers as well as for the health sector to adapt to the demands discussed above. A bibliographic review found great diversity, for example, in the area of emergency care, one of the most complex and haphazard areas [ 12 , 13 , 14 , 15 , 16 ] where this philosophy was applied for process improvement with successful results. Other researchers, such as Guzmán [ 6 ], also showed how, in the last 10 years, general hospital departments published results of process improvement and time optimization in emergency medicine, surgery, pharmacy, nursing, oncology, and administration reflecting the success of having implemented the Lean philosophy.…”
Section: Introductionmentioning
confidence: 99%
“…In Thailand, despite several attempts to promote patient safety in hospitals, patient waiting time remain a significant issue which is mainly due to inadequate hospital quality management systems (Limpanyalert, 2018). Moreover, Zepeda-Lugo et al (2020) identify that further research should evaluate critical success factors in the implementation of Lean within inpatient care. Therefore, this research aims to illustrate the use of Lean tools to reduce inpatient waiting time and to evaluate critical success factors of Lean implementation in an inpatient pharmacy in a Thai public hospital.…”
Section: Introductionmentioning
confidence: 99%